Influence of Appraisal Services on Course Satisfaction among Technical Vocational Education and Training (TVET) Trainees - Maren Awuor Omondi; Pamela Raburu; Peter Aloka (MASI Mandiri Edukasi, 2023)
The study examined the relationship between appraisal guidance services and course satisfaction among trainees in TVET institutions in Kakamega County, Kenya. Concurrent Triangulation design within the mixed methods approach was adopted. Purposive,Â proportionate stratified random, and simple random sampling were used to select 4 TVET institutions, 388 trainees, four registrars, 4 Deputy Principals, and 4 Guidance and Counseling Coordinators. The use of questionnaires and interview schedule collected data. The study established a statistically significant positive correlation between appraisal services (r=.511; p=.000) and course satisfaction among TVET trainees. The appraisal services accounted for 25.8% of the variation in course satisfaction among TVET trainees, respectively. Based on the findings, it was recommended that institutions implement comprehensive and inclusive informational services; Curriculum Development and Certification Council (CDACC) should strengthen the case of career guidance offices in TVET institutions.